Relationship between Academic Achievement and Certain Psychosocial Variables and Gender Differences in Academic Achievement: A Study among Higher Secondary School Students - S, Laiju; , S, Reeja (International Journal of Psychosocial Rehabilitation, 2024)
This study aimed to examine the relationship between academic achievement and certain psychosocial variables, viz., self-esteem, examination anxiety, general stress, and gender differences in the academic performance of higher secondary students. Random sampling technique has been followed for the present study. Self-esteem inventory, Kerala General Anxiety Scale, and Kerala Examination Anxiety Scale were used for the present study. The academic achievement of the students was measured through the marks obtained by the selected higher secondary students in their school examinations. The total sample consists of 150 higher secondary students, which include 75 male and 75 female students. The present study revealed that there exists a substantial relationship between academic achievement and self-esteem. Academic achievement is not related to general anxiety or examination anxiety. There exist gender differences in self-esteem and academic achievement. No significant difference is found in general anxiety and examination anxiety.